STRATEGIC DIRECTIONS OF NATIONAL ENVIRONMENTAL POLICY - Omarov А.Е. (Pressing Problems of Public Administration, 2017)
The paper analyzes priority strategic areas of the state environmental policy of Ukraine: energy security, development of the mineral raw material base of Ukraine, raising the level of environmental safety in the exclusion zone, preservation of natural heritage, safe waste management, new climate policy, reform of the environmental management system, reform of the public environmental control system.